Indonesian Quantitative Easing 2020-2021: Regulation and Comparation with The USA and Japan - Rahman, Diffaryza Zaki; Hutagaol, Henry Darmawan (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
This article is intended to find out how the Quantitative Easing model is implemented in Japan and the United States, how the Quantitative Easing model is applied by Bank Indonesia in 2020 to 2021, and how the Quantitative Easing arrangement is implemented by Bank Indonesia within the framework of Indonesian laws and regulations. This research was conducted using the juridical-normative method by reviewing the literature and the laws and regulations relating to Quantitative Easing in Indonesia. This article is written from research process that conducted by the method of normative-judicial approach. The results showed that Japan implemented Quantitative Easing more broadly by involving the Central Bank's monetary actions in the realm of interest rates and the purchase of securities in the public and private spheres. The United States has a narrower scope by only relying on the purchase of securities or bonds. In Indonesia, Bank Indonesia in 2020-2021 will implement Quantitative Easing to increase liquidity in the banking sector based on the authority given in Law No. 2 of 2020 which is more similar to the Japanese model. This model is known only to be regulated in Law No. 2 of 2020 specifically for handling the economic crisis due to the COVID-19 Pandemic